Carving Mind at Brain’s Joints. The Debate on Cognitive Ontology - Marco Viola (Rosenberg & Sellier, 2017)
Since neuroimaging methods allow researchers to study the human brain at work, the vexed mind-brain problem ceased to be just a metaphysical issue, and became a practical concern for Cognitive Neuroscientists: how could they carve mind and brain into distinct entities, and what is the relation between these two sets? In this paper, I discuss the classical model of one-to-one mappings between mental and neural entities, inherited from phrenology, and make its assumptions explicit. I then examine the shortcomings of this “new phrenology”, and explore two solutions to them: the first accepts many-to-many mappings, whereas the second proposes a radically rethinking of the relata of this correspondence.